1999
DOI: 10.1259/bjr.72.858.10560342
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of MRI with CT for the radiotherapy planning of prostate cancer: a feasibility study.

Abstract: This feasibility study was performed to evaluate the suitability of MRI in defining appropriate pelvic radiotherapy treatment volumes, and to compare MRI sequences with CT for prostate cancer radiotherapy. Five patients with localized prostate cancer, imaged with four MRI sequences (spin echo (SE) T1, turbo SE (TSE) T2, high resolution TSE (HR) T2, and FLASH 3D (F3D)), compared with their corresponding CT planning scans. Segmentation ability of the following pelvic structures: prostatic apex (PA), prostate, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(49 citation statements)
references
References 12 publications
1
48
0
Order By: Relevance
“…the prostate [49], with some studies showing significantly larger target volumes delineated on CT compared with MRI [50]. This may indicate a general overestimation of target size using CT because of a lack of clinical confidence in the extent as a result of relatively poor soft-tissue contrast.…”
Section: Discussionmentioning
confidence: 99%
“…the prostate [49], with some studies showing significantly larger target volumes delineated on CT compared with MRI [50]. This may indicate a general overestimation of target size using CT because of a lack of clinical confidence in the extent as a result of relatively poor soft-tissue contrast.…”
Section: Discussionmentioning
confidence: 99%
“…A first order approach in the use of MR images for planning is simply to ignore tissue inhomogeneities as such, and assign a bulk density equal to 1.0 g/cm 3 to the entire body volume. The influence of this approach on the calculation of dose distributions has been investigated for treatment planning of prostate cancer and brain tumors [6,7,10,11].…”
mentioning
confidence: 99%
“…There are several reasons to expect that MRI would have advantages over other techniques for localizing the prostatic apex, such as the possibility to generate directly images in sagittal and coronal planes and the better soft tissue contrast. This hypothesis has been confirmed by previous studies suggesting sagittal or coronal MRI being the optimal method of localizing the prostatic apex [1,4,9,13,14,18]. Especially Milosevic et al [13] have found sagittal MRI to be beneficial for the apex definition as compared to axial CT.…”
Section: Discussionmentioning
confidence: 56%